Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswadengan Kepercayaan Sebagai Variabel Intervening Pada Fakultas Ekonomi Universitas Islam Kalimantan Banjarmasin - Apriya Santi; Rina (Universitas Lambung Mangkurat, 2019)
Evaluation on the service quality and trust can develop positive perceptions in an effort to provide students’ satisfaction. The purposes of this study are to find out and analyze the effect of service quality on students’ trust, knowing and analyze the effect of trust on students’ satisfaction and analyze the indirect effect of service quality on students’ satisfaction through trust as an intervening variable. With a purposive sampling technique, there are 150 people sampled as respondents. The analysis technique used to test the hypothesis is Structural Equation Modelling. The results showed that service quality has significant effect on students’ trust. The trust has significant effect on the level of students’ satisfaction, but there is no indirect effect of the service quality on students’ satisfaction through students’ trust in the Economics Faculty of the Islamic Kalimantan University.